Hubungan Self-Efficacy Dengan Academic Burnout Pada Mahasiswa Yang Melakukan Pembelajaran Jarak Jauh (PJJ) - Dindiasuvi Auliannisa (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
To reduce the potential for transmission of Covid-19, the Indonesian government has implemented a Large-Scale Social Restrictions (PSBB) policy and recommended physical distancing. This recommendation led to the closure of facilities such as schools or college so that students were required to carry out learning activities remotely. This makes students feel the impact on the implementation of PJJ. One of them is that students experience academic burnout. Therefore, self-efficacy is needed to reduce the increase of academic burnout in student. This study aims to test empirically the relationship between self-efficacy and academic burnout in students who’re doing distance learning. The method used was quantitative method with 246 students as respondents and the sampling technique was purposive sampling. Hypothesis testing was using the Product Moment correlation technique from Pearson. Based on this study, the results of a correlation coefficient of r = -0.343 with a significance value of 0.000 (p ≤ 0.01) indicate that there is a significant negative relationship between self-efficacy and academic burnout in students doing PJJ. The higher the self-efficacy, the lower the academic burnout